Avaliação das resinas de troca iônica (Amberlite IRA 67 e IRA 96) para adsorção de ácido lático obtido a partir do glicerol em coluna de leito fixo - Ferreira, Bruno Burnier Arcanjo (2017)
Lactic acid is one of the main substances that can be obtained from the chemical conversion of glycerol via heterogeneous catalysis. Great attention has now been given to its use in the polymer industry. Monomers of the lactic acid molecule can be used for the production of poly lactic acid which has applications as biodegradable plastics. Thus, it is important to study and optimize lactic acid production, recovery and purification processes. A very promising technology in the separation and recovery of lactic acid consists of ion exchange chromatography, where ion exchange resins that can be easily regenerated are used. Of the advantages that the chromatography presents displays under other processes, it is possible to emphasize the reduction in the consumption of energy, volume of effluents and consumption of chemicals. The aim of this work was to perform a study on the adsorption of lactic acid (obtained from the conversion of glycerol resulting from the production of biodiesel) by ion exchange chromatography using Amberlite IRA 67 and IRA 96 resins. Adsorption isotherms were constructed at temperatures of 30 °C, 40 °C and 60 °C from the breakthrough curves obtained with different concentrations of lactic acid (40 - 160 g/L). With the data of lactic acid concentration for each studied condition, the adjustment of the adsorption isotherm model of Lamgmuir and Henry was made. Studies were also carried out on the separation and purification of a fixed bed column with lactic acid monocomponent solutions, glycerol monocomponent solutions, binary mixtures (lactic acid and glycerol) and real solution obtained from the chemical conversion of glycerol (via heterogeneous catalysis). The Linear Driving Force (LDF) model was used to reproduce the behavior of the breakthrough curves and to estimate mass transfer parameters using commercial gPROMS software. It was possible to conclude that the application of the proposed methodology for separation of lactic acid in fixed bed column presented better results when the temperature of 30 °C in both adsorbents. However, the Amberlite IRA 96 resin was the adsorbent that showed the best results regarding the adsorption capacity and recovery of the lactic acid after the elution step in the adsorption and desorption tests, presenting values of 33.1% (single-component solution), 34, 2% (binary mixture) and 22.9% (real solution). Both resins did not adsorb the glycerol and did not have affinity for this molecule. The model applied to obtain the simulated breakthrough curves for lactic acid under different concentration and temperature conditions predicted the experimental data well.